2015
DOI: 10.1016/j.psi.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Person-centred delivery of mental health information to post-secondary students

Abstract: Mental illnesses are rapidly escalating on university and college campuses. It is well known that postsecondary institutions are not doing enough to address mental health concerns: this represents a significant gap in our attempts to meet the mental health needs of young people. Deficits in mental health knowledge are now proposed as a major contributing factor to both stigma and low service access, but little research has explored this issue. There is also little research to date concerning what young people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Perceptions of mental health issues may also be influenced by comments shared on social media. A key deterrent to seeking treatment for mental health issues is negative perception [6,12], which may stem in part from negative social commentary [13,14]. However, the additivity hypothesis [15] posits that comments that are consistent with a message could boost its persuasive effects, indicating that comments that support using mental health services could reinforce the message.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of mental health issues may also be influenced by comments shared on social media. A key deterrent to seeking treatment for mental health issues is negative perception [6,12], which may stem in part from negative social commentary [13,14]. However, the additivity hypothesis [15] posits that comments that are consistent with a message could boost its persuasive effects, indicating that comments that support using mental health services could reinforce the message.…”
Section: Introductionmentioning
confidence: 99%
“…Mental illness and stress among college students is at an all-time record high with 47% of students reporting symptoms of depression, anxiety, eating disorders, and psychotic symptoms; these symptoms have doubled or tripled since the mid-1990s [4]. With 75% of diagnosable mental illnesses being established between the ages of 15-24 this is a crucial time to provide services and support, however, many go undiagnosed or untreated (Occupational health & wellbeing, 2017).…”
Section: Background Of Emotional Intelligencementioning
confidence: 99%
“…With 75% of diagnosable mental illnesses being established between the ages of 15-24 this is a crucial time to provide services and support, however, many go undiagnosed or untreated (Occupational health & wellbeing, 2017). This highlights a significant gap in meeting the needs of students and it is well-known that post-secondary institutions are not doing enough to address and support mental health concerns [4].…”
Section: Background Of Emotional Intelligencementioning
confidence: 99%
“…In recent research, post-secondary students at a Canadian institution reported negative attitudes towards help-seeking, but had interest in learning about symptoms and coping strategies [7]. Additional Canadian research has shown that mental health literacy programming is context dependent [8] and that there is value in embedding content in regular classes, delivered by the regular teacher [9].…”
Section: Introductionmentioning
confidence: 99%